Space physics guide to STRIDE: Strategies and tactics for recruiting to improve diversity and excellence - Liemohn, Michael W.; Linderman, Jennifer J.; Settles, Isis H. (Frontiers in Astronomy and Space Sciences, 2023)
The space physics research community is not diverse. This is especially true at the senior experience levels, but is even true for our student populations, which are also not matching the demographics of the general public. Striving towards a demographic shift to match the general population promotes equity and inclusion. In addition, diversity increases research productivity. Unfortunately, bias exists, including within the space physics research community, and this negatively impacts hiring practices and perpetuates the demographic mismatch. Yet there are many strategies and tactics that can be adopted to counter this problem. A number of these methods are presented and discussed, specifically those regarding the search process for hiring new research group members. The key methods for achieving an equitable search process are as follows: develop a holistic rubric early, even before the job ad is posted; slow down the downselect from the full applicant pool to the short list of finalists so that the rubric can be carefully applied to each candidate; make the interview process as equitable as possible by considering the ways in which it could be biased; and conduct a fair decision-making process that focuses on the job-relevant criteria and avoids global rankings until the final vote.